Care dependence and caregiver fatigue in ischemic stroke survivors: a cross-sectional study - Shuangyan Tu; Zhiqiang Deng; Siqin Li; Jinyao Wang; Rong Yang; Lihong Zhao (BMC Nursing)
Abstract Background Care dependence among ischemic stroke survivors may be related to caregiver fatigue, but the current status and relationship between these factors have not been well studied. This study aimed to investigate the current status of care dependence and caregiver fatigue in ischemic stroke survivors and to analyze their influencing factors and relationship. Methods A total of 380 pairs of inpatient ischemic stroke survivors and caregivers were included from July 2019 to April 2020 by convenience sample. Survivors demographic data and clinical variables were collected. The Chinese Care Dependency Scale and Fatigue Scale-14 were used to assess survivors’ care dependence and caregiver fatigue. Results The largest number of ischemic stroke survivors were mild care dependence (62.89%), followed by those who were severe dependence (19.47%). Caregiver fatigue was moderate (42.9%) or severe (40.5%). Survivors’ care dependence was influenced by the age of survivors (P = 0.005), total score of NIHSS (P < 0.001), and number of comorbidities (P = 0.006). Caregiver fatigue was positively correlated with survivors’ care dependence (P < 0.001), and was affected by total score of NIHSS (P = 0.032), conscious health (P = 0.024) or sleep status (P < 0.001) of caregivers, and number of survivors cared for at the same time (P = 0.002). Conclusions The current status of ischemic stroke survivors’ care dependence and caregiver fatigue was not optimistic. This study identified three influencing factors for IS survivors’ care dependence and four influencing factors for caregiver fatigue, and identified the positive relationship between them. This provided new evidence and direction for future research to explore effective measures to reduce survivors’ care dependence and caregiver fatigue. In clinical practice, we should focus on and actively help survivors and caregivers with these influencing factors to reduce their burden. Trial registration This study was not registered prospectively and we would conduct retrospectively registered. Clinical trial number Not applicable.